FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PEMBATASAN CAIRAN PASIEN GAGAL GINJAL TERMINAL YANG MENJALANI HEMODIALISIS DI SATU RUMAH SAKIT SWASTA DI INDONESIA BARAT [FACTORS ASSOCIATED WITH ADHERENCE TO FLUID RESTRICTION TOWARDS PATIENTS WITH END STAGE RENAL DISEASE UNDERGOING HEMODIALYSIS IN A PRIVATE HOSPITAL, WEST INDONESIA] - Eva Chris Veronica Gultom; I Made Kariasa; Masfuri Masfuri (Nursing Current: Jurnal Keperawatan, 2020)
End Stage Renal Disease is the final stage of the Chronic Kidney Disease (CKD) with a Glomerular Filtration Rate (GFR) value of less than 15 ml / min / 1.73m². End Stage Renal Disease can be treated with hemodialysis therapy (National Kidney Foundation, 2015; Thomas, 2014). The hemodialysis provides fluid resctrictions for patients who undergo. There are many factors that make fluid restrictions adherence difficult to do. (Chironda&Bhengu, 2015). The biggest and dominant factor is psychological factor, which is self compassion. Self compassion is the attitude of giving compassion to ourselves, so that when a patient undergoing hemodialysis in difficult conditions is able to assume the situation is the same as other people, and does not punish themselves and have motivation in undergoing a therapeutic regimen. The purpose of this study was to identify factors that have corelation to fluid adherence in end stage renal disease patients undergoing hemodialysis. This study used a cross sectional method, with 89 end stage renal disease patients who underwent hemodialysis three times a week and who were selected using a purposive sampling technique. The results showed that the majority of patients had high self compassion (69.7%). The corelation of self compassion with fluid adherence was not significant (p=0,076), other factors affecting fluid adherence were age (p=0.033), gender (p= 0,937), marital status (p = 0.473), working status ( p = 0,885), level of education (p= 0,126), length of undergoing hemodialysis (p = 0,425), and social support (p =0,206) The results of multivariate analysis showed that the most dominant factors related to fluid restriction adherence was age. This research is expected to be a reference for nurses in developing nursing studies in end stage renal disease patients undergoing hemodialysisBAHASA INDONESIA ABSTRAK: Gagal ginjal terminal merupakan tahap akhir dari kondisi Chronic Kidney Disease (CKD) dengan nilai Glomerulus Filtrasi Rate (GFR) kurang dari 15 ml/menit/1,73m². Gagal ginjal terminal dapat ditangani dengan terapi hemodialisis. Adanya hemodialisis ini memberikan pembatasan cairan pada pasien yang menjalaninya. Kepatuhan pembatasan cairan pada sebagian pasien sulit untuk dilakukan dengan alasan banyak faktor, yakni usia, jenis kelamin, tingkat pendidikan, status bekerja, lama menjalani hemodialisis, status menikah, dan dukungan sosial. Faktor yang terbesar dan dominan adalah faktor psikologis, yakni self compassion. Self compassion merupakan sikap memberikan belas kasih kepada diri sendiri, sehingga ketika seorang pasien yang menjalani hemodialisis dalam kondisi sulit mampu menganggap situasinya adalah sama dengan orang lain, dan tidak menghukum diri sendiri serta memiliki motivasi dalam menjalani regimen terapi. Tujuan penelitian ini adalah untuk mengidentifikasi faktor-faktor yang berhubungan dengan kepatuhan pembatasan cairan pasien gagal ginjal terminal yang menjalani hemodialisis. Penelitian ini menggunakan metode cross sectional, sebanyak 89 pasien pasien gagal ginjal terminal yang menjalani hemodialisis dalam tiga kali seminggu yang dipilih menggunakan teknik purposive sampling. Hasil penelitian menunjukkan bahwa mayoritas pasien memiliki self compassion tinggi (69,7%). Hubungan self compassion dengan kepatuhan pembatasan cairan tidak signifikan (p=0,076), faktor lain yang mempengaruhi kepatuhan pembatasan cairan adalah adalah usia (p=0,033), jenis kelamin (p=0,937), status menikah (p=0,473), status bekerja (p=0,885), tingkat pendidikan (p=0,126), lama menjalani hemodialisis (p=0,425), dan dukungan sosial (p=0,206). Hasil analisis multivariat menunjukkan faktor yang paling dominan berhubungan dengan kepatuhan pembatasan cairan adalah usia. Penelitian ini diharapkan dapat menjadikan acuan bagi perawat dalam mengembangkan pengkajian keperawatan pada pasien gagal ginjal terminal yang menjalani hemodialisis.